Dialectally-sensitive norms of the Spanish version of Main Concept Analysis (Span-MCA) for quantifying neurogenically impaired spoken discourse - Kong, Anthony Pak-Hin (Revista de Investigación en Logopedia, 2021)
Aphasia is an acquired language impairment caused by damage in the regions of the brain that support language. The Main Concept Analysis (MCA; Kong, 2016b) is a published formal assessment battery that allows the quantification of the presence, accuracy, completeness, and efficiency of content in spoken discourse produced by persons with aphasia (PWA). It utilizes a sequential picture description task (with four sets of pictures) for language sample elicitation. The MCA results can also be used clinically for targeting appropriate interventions of aphasic output. The purpose of this research is to develop a Spanish adaptation of the MCA (i.e., Span-MCA) by establishing normative data based on native unimpaired speakers of Spanish from four different dialect origins (Central American Caribbean, Andean-Pacific, Mexican, and Central-Southern Peninsular regions). A total of 91 unimpaired participants that consisted of different age groups, education levels, and dialect origins were recruited to establish four sets of dialect-specific norms and scoring criteria of Span-MCA, including target main concepts and corresponding lexical items related to the picture sets. The Span-MCA was also applied to one pilot native Spanish PWA. The normative data suggested that speakers who were younger or with a higher level of education levels produced significantly more accurate and complete main concepts in their spoken discourse. The application of Span-MCA to the pilot native Spanish PWA successfully identified impaired performance, as compared to the dialectally-sensitive norms established in this study. This study highlighted the clinical value of Span-MCA as a supplement to evaluate spoken discourse and target intervention by speech-language pathologists and related healthcare practitioners.
Keywords: Main Concept Analysis; spoken discourse; dialectally-sensitive norms; Spanish